Vulgarisin-type diterpenoids from self-heal (Prunella vulgaris) and their neuroprotective effects against ischemia/reperfusion (I/R) via a mitochondria-related pathway. Issue 13 (9th June 2022) - Ma, Fengwei; Deng, Qingfang; Lou, Huayong; Li, Jinyu; Xu, Su; Wu, Wenneng; Wen, Qihua; Tang, Lei; Wang, Xin; Pan, Weidong
Abstract : Twelve vulgarisin-type diterpenoids were obtained from self-heal. Their absolute configurations were elucidated. These vulgarisin-type diterpenoids possess neuroprotective effects. Abstract : Self-heal ( Prunella vulgaris L.) is a perennial edible plant that is widely distributed across the world and is traditionally consumed as a food additive in soft drink beverages. In this study, to explore the functional components of P. vulgaris, an investigation of its ethanol extracts has been conducted by our group. As a result, twelve (1–12 ) vulgarisin-type diterpenoids with a special 5/6/4/5-fused ring skeleton, including six new ones (1–6 ), were obtained. Their structures including the absolute configuration were elucidated based on comprehensive spectroscopic evidence, ECD calculations, as well as single-crystal X-ray diffraction analyses. All the isolates were tested for neuroprotective effects against ischemia/reperfusion (I/R) on primary neuron cells through the oxygen and glucose deprivation and reperfusion (OGD/R) induced injury model. The results showed that all twelve vulgarisin-type diterpenoids possess promising neuroprotective activity at a concentration of 10 μM. Among them, compound 3 can significantly suppress cell apoptosis by regulating Bax/Bcl-2 protein expression and inhibiting cleaved caspase-3 and caspase-9 expression with a western blotting assay. Further research revealed that compound 3 could improve mitochondrial function by inhibiting mitochondrial cytochrome c release, reducing ROS levels, and maintaining the membrane potential. This work firstly reports vulgarisin-type diterpenoids possessing neuroprotective activity. These findings also suggest that daily consumption of P. vulgaris might prevent cerebral disorders via a mitochondria-related pathway.